Ginkgo biloba: A ‘living fossil’ with modern day phytomedicinal applications - Abdulmumin A. Nuhu (Journal of Applied Pharmaceutical Science, 2014)
Ginkgo biloba has survived for over 200 million years now. With other members of this gymnosperm extinct, it is considered as a ‘living fossil’. Yinxing, as it is called in Chinese, is very popular in East Asia as a remedy for lung congestion, ischemia and asthma. In modern day medical practice, growing consideration is given to the extract from this tree as a line of treatment in many cancer conditions partly due to the side effects of conventional drugs of therapy. The extract has also anti-diabetic, anti-inflammatory and cardio- and hepatoprotective roles. These and other numerous recent applications of this important botanical drug are discussed in this review.
Keywords: Ginkgo biloba, EGb 761, Phytomedicinal applications, Botanical drug.